Truck scheduling in a cross docking systems with fixed due dates and shipment sorting. (March 2018) - Molavi, Danyar; Shahmardan, Amin; Sajadieh, Mohsen S.
Highlights: Truck scheduling in a two-touch cross-dock with hard due dates for outbound trucks. Due date can be adjusted along a time-window without affecting customers' needs. Identifying limits of this time window is the key to optimize cross-dock operations. Numerical results indicate the impact of shipment sorting on cross-dock performance. Abstract: In this paper, a truck scheduling problem is investigated at a two-touch cross-docking center with due dates for outbound trucks as a hard constraint. The objective is to minimize the total cost comprising penalty and delivery cost of delayed shipments. The sequence of unloading shipments is considered and it is assumed that shipments are sent to shipping dock doors immediately after unloading where a First-In-First-Out (FIFO) policy is considered for loading the shipments. A mixed integer programming model is developed for the proposed model. A hybrid genetic algorithm-reduced variable neighborhood search (HGARVNS) algorithm is developed to solve the problem in medium and large sized scales and compared with common meta-heuristic algorithms used in literature. The numerical results show that the due date can be adjusted between a time-window or postponed to a certain point based on customers' needs or cross-dock limitations. Moreover, we concluded that the sorting of shipments inside inbound trucks can improve the cross-dock performance.